Pensamiento formal y rendimiento en física. Análisis de la validez del test de Longeot por referencia a tests de rendimiento - López Rupérez, F.; Palacios Gómez, C.; Brincones Calvo, Isabel; Garrote Flores, R.; Sánchez González, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This study investigated the influence of psychological factors, such as general fluid intelligence, measured by Rayen Progressive Matrices Test, or cognitive development measured by Longeot test, on the achievement in a High School Physics course. A previously analyzed set of five different tests with twenty five items, multiple-choice each, was used. The convergent validity and the predictive power of the Longeot test in relation to physics tests was examined. Finally, the implications for Physics teaching are discussed.